Culture and social resistance to reform: A theory about the endogeneity of public beliefs with an application to the case of Argentina - Sergio Pernice; Federico Sturzenegger (Universidad del Centro de Estudios Macroeconómicos de Argentina (UCEMA), 2004)
This paper attempts to understand the factors that explain the degree of support or criticism that a reform process may be subject to. Understanding these determinants is critical, in turn, to assess the feasibility and sustainability of those reforms. In particular, we want to assess what are the elements that create societal consensus for reform and which are the main factors that turn public opinion against it. In the case of Argentina, for example, such dynamics are critical to understand how public opinion imposed constraints on government behavior, affected macroeconomic performance, and ultimately, determined the chance of success of reforms.
Keywords: 330; Reform; Öffentliche Meinung; Argentinien